2012
DOI: 10.1007/s00296-012-2453-x
|View full text |Cite
|
Sign up to set email alerts
|

The factors considered as trigger for the attacks in patients with familial Mediterranean fever

Abstract: Although the inflammatory cascade of familial Mediterranean fever (FMF) is partially understood, triggering factors of those attacks has not been studied well. It is supposed that physical stresses such as cold exposure, tiredness and emotional stresses could provoke attacks. This study is aimed to survey the factors regarded as triggering the attacks in patients with FMF and their relationship with MEFV gene mutations. Clinical findings and genetic mutations (consist of M694V, M694I, M680I, V726A, E148Q) of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 14 publications
1
29
0
2
Order By: Relevance
“…Recognised trigger factors include physical or emotional stress, menstruation, physical trauma, exposure to cold, infections, inflammation, high fat intake, starvation, sleeplessness and tiredness 47. These triggers may differ depending on the type of attack 48 49. Some authors recommend increasing the dose of colchicine to pre-empt trigger events 50 51…”
Section: Resultsmentioning
confidence: 99%
“…Recognised trigger factors include physical or emotional stress, menstruation, physical trauma, exposure to cold, infections, inflammation, high fat intake, starvation, sleeplessness and tiredness 47. These triggers may differ depending on the type of attack 48 49. Some authors recommend increasing the dose of colchicine to pre-empt trigger events 50 51…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between the menstrual period and FMF attacks is controversial . Takano et al confirmed changes in hydrogen and potassium excretion in urine during the menstrual cycle .…”
Section: Discussionmentioning
confidence: 99%
“…Şimdiye kadar atakları tetikleyen birçok faktör tanımlanmıştır. Ülkemizde bu konu ile ilgili bir çalışmada AAA hastalarında serozit ataklarını tetikleyen en sık etkenin soğukla karşılaşma (%59,9) olduğu, psikolojik stresin (%49,8) ve fiziksel yorgunluğun (%40) bunu izlediği, en nadir sebebin ise travma (%1,5) olduğu saptanmıştır (4). Olgumuzda da travma, ve/veya bunun sebep olduğu psikolojik stresin AAA atağına sebep olabildiği düşünülmüştür.…”
Section: Discussionunclassified